PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA ( StudiKasusPada Karyawan PT. Taspen (Persero) KUC Malang ) - Nurul Hidayat (Jurnal Administrasi Bisnis, 2013)
Situational leadership style is the style or ways of leadership shown by a leader to guide, implement, direct, encourage subordinates to achieve the goals and optimally utilize all its capabilities by combining the existing situation with regard to the behavior of leaders and subordinates. Organizational culture is the habits that occur in the organizational hierarchy representing behavioral norms are followed by the members of the organization. Organizational culture is spread belief system and values ​​that develops within an organization and directing the behavior of its members. Job satisfaction reflects one's feelings toward his work, is seen in the positive attitude of employees towards work and everything encountered in their work environment. This study aimed to determine the effect of situational leadership style and organizational culture on Job Satisfaction PT. Taspen (Persero) KUC Malang. Situational Leadership Style variables significantly influence job satisfaction of 48.0%. Organizational Culture variables significantly influence on Job Satisfaction of 17.7%. Based on the analysis of known coefficient of determination value of Adjusted R Square of 0.488, which means 48.8% variable job satisfaction is influenced by variables situational leadership style and organizational culture.   Key word : situational leadership, organizational culture, job satisfaction